Ormas Islam Bermuatan Politik Yang Terlarang Di Indonesia - Mahmuda mahmud muda (UIN Mahmud Yunus Batusangkar, 2022)
Ormas is a community organization that contributes to the nation and the Republic of Indonesia. The state guarantees the freedom of an individual in forming a community forum in order to contribute to society both in the field of religion, social, economic, and in the form of legal protection. The implementation of mass organizations gives a good contribution to the country where the state also requires the role of community activity in controlling the state.The implementation organization is certainly left to the people involved in running the organization in accordance with the vision and mission and objectives of the organization of religion. In this case, the author sees the existence of religious organizations mixed with the politicization of the nation and the state of Indonesia. The existence of such organizations has violated state rules that have an impact on the instability of the state both in political pawns and terms religious freedom.The Islamic organizations that have been banned include HTI ( Hizb ut-Tahrir Indonesia ), and FPI (Islamic Defenders Front ). Both Islamic organizations have been banned because it contradicts the prinsipal to maintain the stability of the country. In this research, the author will see the extent to which the organization has been banned by the state in activities so that the state has legally strictly prohibited the activity of organizations for the people of Indonesia